Pengaruh Aromaterapi Lavender terhadap Kecemasan pada Pasien Pra-Operasi Sectio Caesarea dengan Anestesi Spinal - Sari, Melya; Yuliastuti, Estin; Widyastuti, Yuli; Handoyo, Dwi (Jurnal Kesehatan, 2023)
Anxiety in preoperative caesarean section patients is usually caused by worries about themselves and their baby's condition. Lavender aromatherapy is a complementary therapy and non-pharmacological technique to reduce anxiety. The aim of this study was to determine the effect of lavender aromatherapy on anxiety in preoperative caesarean section patients with spinal anesthesia. This study was a quantitative study that used experimental methods with a one-group pretest-posttest design. The sampling technique in this study was purposive sampling with a sample of 22 respondents. The instrument used was APAIS (The Amsterdam Preoperative Anxiety and Information Scale). Data analysis was performed using the Wilcoxon statistical test. This study obtained a result of a p-value=0.000 (<α 0.05). This means that lavender aromatherapy has an effect on reducing anxiety levels in preoperative caesarean section patients. Lavender oil has a relaxing effect on nerves and muscles tension.